Manufacturing sector development and it's export growth - Ravindran, Suthakaran (2000)
Malaysia has transformed from commodity based economy to a manufacturing based economy for the past two decades. The good performance of manufacturing sector had lead Malaysia penetrate > international market and changed its strategy to export promotion. Manufacturing sector in Malaysian achieved the most rapid economic growth in the past few years. Nevertheless, there are still some 'bottle necks' in achieving extensive export growth in international market. This study whenever possible takes the effort to capture the ideas of major factors that exhilarating and demoting export growth in Malaysian Manufacturing sector. About seven internal and external variables are identified for the purpose of this study. They are Foreign Direct Investment (FDI), Exchange Rate (ER), Tariff (TP), Productivity level (P), Wage Rate (WR), Economic Growth (EO) and Export Price (EP). The primary mission of this study is to analyze the relative importance of factors that significantly contributed to manufacturing goods export growth in Malaysia. The objective of the study is achieved by estimation of Vector Error-Correction Model (VECM). The data for the study consists of quarterly observations from 1980: 1 to 2000:1. The result shows that, there are direct and indirect causality linkages among the variables in determining the export growth. Both the external and internal factors are equally important in construction the export growth in Malaysia. In general the findings shows that external factors are relatively play an important role in explaining the growth of manufacturing export goods in international market. The external shocks are predicted to effect the manufacturing export extremely. On the other side, the internal factors also influencing export due to the chain reaction that brought by the external factors.